Dynamics Modeling and Coupling Characteristic Analysis of Tracked Vehicle Gearbox - Zheng Zhang; Guangbin Feng; Huagang Sun (Jixie chuandong)
The gearbox is one of the core components of the tracked vehicle. In order to accurately describe the internal coupling characteristics during the operation of the gearbox, based on the establishment of the multi-rigid model of the gearbox, the box, the drive shaft and the bearing are flexibly，the gearbox rigid-flexible coupling dynamics simulation model is established. Taking a practical working condition as an example, the variation law of the dynamic meshing force of the gear pair in rigid mode and rigid-flexible coupling mode is compared and analyzed, and the time-frequency domain curves of the load characteristics of each drive shaft and the surface acceleration of the box are obtained. By using the bench test, the accuracy of the gearbox rigid-flexible coupling model is verified. The simulation process and results provide a model and theoretical basis for the study of gearbox condition monitoring and fault diagnosis for subsequent tracked vehicles.